2019
DOI: 10.19027/jai.18.2.152-161
|View full text |Cite
|
Sign up to set email alerts
|

Profile of 17ß-estradiol, vitellogenin, and egg diameter during gonad maturation process of striped catfish Pangasianodon hypophthalmus

Abstract: This study was conducted to evaluate the profile of 17ß-estradiol (E2) and vitellogenin (Vtg) in plasma and egg diameter during gonad maturity process of striped catfish Pangasianodon hypophthalmus. Blood samples were collected from immature striped catfish, male and female with different stage of gonad maturity (stage I, II, III, and IV) to measure the concentrations of E2 and Vtg. Gonad maturity development of striped catfish was observed based on egg diameter. Result showed that E2 concentrations were the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
0
0
Order By: Relevance
“…because when the vitellogenesis process takes place, the yolk granules increase in number and size, so that the volume of the oocyte becomes enlarged (Pamungkas et al, 2019). The induction of spawnprim hormone in Siamese catfish also showed a positive response regarding weight gain of the fish broodstock because the spawnprim hormone increases the appetite of the fish (Islami et al, 2017), which also shown in this study.…”
Section: Spawnprim Dosage Replication Day 20supporting
confidence: 75%
“…because when the vitellogenesis process takes place, the yolk granules increase in number and size, so that the volume of the oocyte becomes enlarged (Pamungkas et al, 2019). The induction of spawnprim hormone in Siamese catfish also showed a positive response regarding weight gain of the fish broodstock because the spawnprim hormone increases the appetite of the fish (Islami et al, 2017), which also shown in this study.…”
Section: Spawnprim Dosage Replication Day 20supporting
confidence: 75%
“…It was found that the estradiol-17β and testosterone levels were significantly higher in the gonads of cockle (Fulvia mutica) during gametogenesis and spawning [67]. The highest levels of estradiol-17β were found in the blood of sexually mature females striped catfish (Pangasianodon hypophthalmus) [68]. Sexual maturation of male mice stimulated the expression of enzyme FADS1, a key rate-limiting enzyme of ARA synthesis from its substrate LA [69].…”
Section: Discussionmentioning
confidence: 99%